Pre-service biology teachers’ knowledge of the 21st-century skills and its associated instructional models: The Indonesian context - Ummi Nur Afinni Dwi Jayanti; Miza Nina Adlini; Yassir Ni’ma Rangga Wiryawan (University of Muhammadiyah Malang, 2024)
Integrating the 21st-century skills into Indonesia’s education system is crucial for equipping students to face future challenges. This study investigates the knowledge of pre-service biology teachers in Indonesia regarding the 21st -century skills and their understanding of instructional models that support skill development. Conducted from March to September 2024, the research employed a cross-sectional survey design with a total sampling technique, involving 78 students from a Biology Education program at a public Islamic university in North Sumatra, all of whom had completed a course on biology learning strategies. Data were gathered using questionnaires and analyzed quantitatively to determine key trends. The findings indicate that although most students recognize the significance of the 21st-century skills in biology education, their understanding is limited. Only a small number could identify all essential skills, with creative thinking being the most recognized. Students were well-acquainted with project-based learning as a model for developing these skills but had limited knowledge of the structure and application of other instructional models, such as discovery and inquiry learning. These findings emphasize the need for curriculum improvement to deepen students’ comprehension of various instructional models and the integration of diverse information sources, enabling more effective integration of the 21st -century skills into biology education.